PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN KAWASAN AGROPOLITAN PROGRAM PADAT KARYA TUNAI DI DESA TASIKMADU KECAMATAN PALANG KABUPATEN TUBAN - Winda Ayuning Lestari; Eny Lestari; Eksa Rusdiyana (AGRITEXTS: Journal of Agricultural Extension, 2019)
This research aims to analyze the level of community participation in the development of the agropolitan area Cash for Works Program, analyzing internal factors and external factors that influence community participation; and analyze the relationship between internal factors and external factors of participation with the level of community participation in the development of the agropolitan area Cash for Works Program in Tasikmadu Village, Palang District, Tuban Regency. This study uses quantitative methods with survey techniques. The research location is in Tasikmadu Village, Palang District, Tuban Regency because there is an agropolitan area of star fruit plantation. The sampling technique by multistage cluster random sampling was 69 respondents. Data analysis using Spearman Rank correlation test. The results of the study showed: (1) Age of the community included in the category of age 36-55 years, with an average level of education graduating from high school / equivalent, land ownership area ≤ 0.3 ha, income level of the agricultural sector>2.1 million, length live on average>21 years, with the level of cosmopolitan including very low category and stakeholders including quite active category. (2) The level of community participation is included in the category of moderate participation and is on the consultation ladder. (3) Spearman's Rank correlation test shows that internal and external factors that are significantly related to community participation are the extent of land ownership, income level and the level of cosmopolitan, while age, education level, length of stay, and stakeholders are not significantly related.